Pendampingan Penyusunan DED Rumah Produksi Bersama Sentra IKM Olahan Hasil Laut untuk UMKM Kota Pangkalpinang Provinsi Kepulauan Bangka Belitung - Miskar Maini; Rahmat Kurniawan; Junita Eka Susanti; Syahidus Syuhada; Ayudia Hardiyani Kiranaratri; Hermon Frederik Tambunan; Reza Asriandi Ekaputra; Erdina Tyagita Utami; Galih Rio Prayogi; Ayu Sinta Aprilia; Ilpandari Ilpandari (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
In an effort to improve people's welfare through trade and service-based development supported by superior industry, special attention is given to the seafood processing industry in Pangkalpinang City. One of the infrastructure support systems needed to support UMKM-based seafood trade activities is the provision of standardized production facilities that can be used jointly by UMKM players. This service program aims to support the industry through technical assistance in planning the construction of Production Houses with IKM Centers. This facility is designed to provide production facilities that meet UMKM standards in order to strengthen trade based on superior industries. Assistance includes field observations, structural and technical analysis, and cost calculations to ensure optimal building design that meets needs. The building design uses a concrete structure and steel roof, with local cultural elements in the form of a gable roof and carved wooden plank typical of Bangka Belitung. The estimated cost of building construction is IDR 4,572,000,000.00 (four billion five hundred and seventy-two million rupiah)